International trade and polarization in the labor market - Satya P. Das (Economics: The Open-Access, Open-Assessment E-Journal, 2012)
The paper builds an argument that international trade can be an explanation behind polarization of employment in the labor market observed in developed countries such as UK and US It considers a small open economy, having production sectors which use three types of labor: high-skill, middle-skill and low-skill. The economy faces an increase in the relative price of the high-skill intensive sector. Using decision rules for choosing high-skill, middleskill and low-skill education, it is shown that such a terms-of- trade shock can lead to polarization: shrinkage of middle-skill jobs, combined with higher shares of high-skill as well as low-skill workers in the total workforce. The effects of off-shoring on wages and job composition are also studied. Off-shoring of low-skill and high-skill tasks, not middle-skill tasks, is shown to contribute towards polarization in job composition.
Keywords: F16; J21; 330; polarization in labor markets; hollowing out; wage inequality; skill biased technical change; terms of trade; off-shoring